Novel hybrid OVSF-TH-UWB communication system - ZENG Fan-zi; TUO Ying-ying; LUO Juan; LI Ren-fa (Tongxin xuebao)
A hybrid OVSF-TH-UWB based OVSF-code was proposed, and a corresponding correlation mask was designed.Both performance analysis and simulation results prove that OVSF-TH-UWB system can effectively reduce the multi-users-interference and Gaussian noise interference, and its performance is better than those of 2PPM-TH and DS-UWB system.